THE EFFECT OF HIGH TEMPERATURE HEATING ON WEIGHT AND COLOR CHANGES IN COMPOSITE RESIN AS FORENSIC IDENTIFICATION - Farhan Jordan Akbar; Ira Anggar Kusuma; Tuntas Dhanardhono; Yoghi Bagus Prabowo (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: Fire disaster is a non-natural disaster that often occurs. The impact is that victims are difficult to identify. One of the identification methods that can be used is dental restorative materials with observing changes in color and weight that occur in dental restorative materials due to exposure to high temperatures. Composite resin is a dental restorative material that is often used because it has good aesthetics, physical and mechanical properties. Purpose: This study to determine the effect of high temperature on weight and color changes in nanohybrid and bulkfill composite resin as a reference for forensic identification. Method: This research is an experimental laboratory with a pre and post-test control group design. A total of 30 nanohybrid composite resin samples and 30 bulkfill composite resin samples were divided into 5 groups consisting of 4 treatment groups and 1 control group. The treatment group was heated at four temperature groups, 30°C-200°C, 30°C- 400°C, 30°C-800°C and 30°C-1100°C using a furnace (Thermo Scientific, USA). Weight changes were measured using a digital scale (Ohaus,China) and color changes were observed using the Shade Guide (Vitapan Classical, Germany). Result: A change in color and weight of the nanohybrid composite resin and bulkfill after being heated at high temperatures. Two-Way ANOVA test and Post Hoc LSD test showed that there was a significant difference in weight between nanohybrid composite resin and bulk fill composite resin at each temperature interval (p<0.001). Conclusions: High temperature heating affects the color and weight changes of nanohybrid and bulkfill composite resin. Keywords: Bulkfill composite resin, High temperature heating, Nanohybrid composite resin